Bacterial salivary microbiome associates with asthma among african american children and young adults. Issue 12 (9th September 2019) - Espuela‐Ortiz, Antonio; Lorenzo‐Diaz, Fabian; Baez‐Ortega, Adrian; Eng, Celeste; Hernandez‐Pacheco, Natalia; Oh, Sam S.; Lenoir, Michael; Burchard, Esteban G.; Flores, Carlos; Pino‐Yanes, Maria
Abstract: Several studies have shown that the airways of asthma patients contain higher diversity of bacteria and are enriched in pathogenic species. However, sampling the airways in children is challenging. Here we aimed to identify differences in the salivary bacterial composition between African Americans children with and without asthma. Saliva samples from 57 asthma cases and 57 healthy controls were analyzed by means of 16S ribosomal RNA amplicon profiling. Measurements of bacterial diversity and genus relative abundance were compared between cases and controls using the nonparametric Wilcoxon test and multivariate regression models. A total of five phyla and a mean of 56 genera were identified. Among them, 15 genera had a relative abundance greater than 1%, being Prevotella, Haemophilus, Streptococcus, and Veillonella the most abundant genera. Differences between cases and controls were found in terms of diversity, as well as in relative abundance for Streptococcus genus (13.0% in cases vs 18.3% in controls; P = .003) and Veillonella genus (11.1% in cases vs 8.0% in controls; P = .002). These differences remained significant after correction for multiple comparisons and when potential confounders were taken into account in logistic regression models. In conclusion, we identified changes in the salivary microbiota associated with asthma among African Americans.